2010
DOI: 10.17221/22/2010-pse
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal emergence of selected summer annual weed species in dependence on soil temperature

Abstract: This study aimed to describe emergence cycles of selected weed species under Central European conditions in relation to cumulative soil temperatures from the start of the vegetation season. Emergence of Chenopodium album, Echinochloa crus-galli, Galinsoga ciliata, and Abutilon theophrasti was observed from March to October during the period 2001-2006 at two locations. The beginning of main field emergence was determined as the day when the sum of effective hour temperatures was achieved, and was detected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Weed emergence before flame weeding appeared to be stimulated by the 6 mm precipitation after the first drilling (Table 1 and Figs 3 and 4) in 2009. However, the otherwise very dry weather conditions in this year may explain the lower average flame weeding effects compared with 2008, because dry soil conditions delay and slow weed emergence (Jursik et al. , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Weed emergence before flame weeding appeared to be stimulated by the 6 mm precipitation after the first drilling (Table 1 and Figs 3 and 4) in 2009. However, the otherwise very dry weather conditions in this year may explain the lower average flame weeding effects compared with 2008, because dry soil conditions delay and slow weed emergence (Jursik et al. , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of weed incidence in separate crops of the rotation shows that in 2008 the prolonged drought lasting from April 20 to June 16 (57 days with the amount of precipitation as low as 15.6 mm) resulted in a low weed incidence in the crops of winter triticale (Table 1). Literature sources indicate that weed incidence in field crops is determined by meteorological conditions, especially the amount of precipitation in spring (Auškalnienė, 2006;Deveikytė et al, 2008) and soil moisture (Jursík et al, 2010). Analysis of variance indicated that soil tillage method had a significant impact on the weed incidence in winter triticale crops (the amount of weeds F act.…”
Section: Resultsmentioning
confidence: 99%